2012
DOI: 10.1371/journal.pone.0051407
|View full text |Cite
|
Sign up to set email alerts
|

Histone Demethylase Jumonji D3 (JMJD3) as a Tumor Suppressor by Regulating p53 Protein Nuclear Stabilization

Abstract: Histone methylation regulates normal stem cell fate decisions through a coordinated interplay between histone methyltransferases and demethylases at lineage specific genes. Malignant transformation is associated with aberrant accumulation of repressive histone modifications, such as polycomb mediated histone 3 lysine 27 (H3K27me3) resulting in a histone methylation mediated block to differentiation. The relevance, however, of histone demethylases in cancer remains less clear. We report that JMJD3, a H3K27me3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 46 publications
5
75
0
Order By: Relevance
“…KDM6B can directly associate with key transcription factors, such as p53 (67,68), p65, and p50 NF-KB subunits (37) and STAT (69,70) and SMAD (71) family members, enhancing their functions. In turn, a reciprocal mode of regulation Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…KDM6B can directly associate with key transcription factors, such as p53 (67,68), p65, and p50 NF-KB subunits (37) and STAT (69,70) and SMAD (71) family members, enhancing their functions. In turn, a reciprocal mode of regulation Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…However, the genetic lesion is rather poorly correlated with mutations in TP53 (35). Deregulation of JMJD3 may contribute to gliomagenesis by inhibiting the p53 pathway with obstruction by terminal differentiation (37). Thus, KDM6B may be a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…KDM4A promotes cellular transformation through transcriptional repression of the tumor suppressor CHD5 (69), and KDM6B has been found to promote the epithelial-mesenchymal transition (70). Conversely, others have demonstrated that KDM6B acts as a tumor suppressor by regulating p53 nuclear stabilization (71). In colorectal cancer, depletion of KDM5B induced cellular senescence (72).…”
Section: Discussionmentioning
confidence: 99%